Gandhian Economic Order-Building an Alternate to Globalisation - Kumar, Raj; Chandel, Kulbhushan (Prabandhan: Indian Journal of Management, 2009)
World has experienced, the great economic depression in the year 1929. Today, in the year 2008, world is again passing through the stage of a big economic recession, which has its originating roots in the developed world. During the period of great depression, the world trade was declined by 60 percent whereas during the current economic recession, the trade and economic activities have suffered substantially. The fundamental difference in the great depression and in the present economic recession is that, the former has taken place in the colonial era whereas the later has occurred in the Globalized era. The present economic crisis has been deeply affected by the economies of the world but the Indian economy has been able to minimize the negative impacts of current crisis due to its strong agricultural base. The Globalization has brought many social, cultural, economical and political evil effects with it. In turn, it requires a viable model to address all these problems. In this paper an attempt has been made to study Gandhian Economic Order as an alternative to the Globalization. The main objective of the research paper is to analyze the relevance of Gandhian Economic Thoughts as an alternative of the Globalization. It is observed that Gandhi never favored such form of Globalization Which is based on the philosophy of exploitation and violence. He advocated that form of Globalization where the culture of peace, love, happiness, nonviolence, harmony, mutual trust respect and prosperity coexists along with each other.